Sources of Knowledge Used by Entrepreneurial Firms in the European High-Tech Sector - Sara Amoroso; David B. Audretsch; Albert N. Link (European Commission, Joint Research Centre (JRC), 2017)
The purpose of this paper is to explore the relationship between an entrepreneurâ exteuro™s experience and education and his/her reliance on alternative sources of knowledge for exploring new business opportunities. The extant literature that is at the crossroads between sources of knowledge and the experiential and intellectual base of an entrepreneur (i.e., dimensions of his/her human capital) suggests that it is through experience and through education that an entrepreneur obtains knowledge. Using information on a sample of high-tech manufacturing firms across 10 European countries, we explore heterogeneities in the influence of experience, age, and education of the firmâ exteuro™s primary founder on the perceived importance of (i.e., use of) alternative sources of knowledge. We find that the association of these characteristics differs significantly across sources of knowledge, and across European regions. Education is positively related to the importance of knowledge from research institutes and internal know-how, while age is negatively related to the importance of research institutes and positively related to publications and conferences. On the one hand, in South/East European countries, the importance of internal know-how is positively associated with age and education, but negatively associated with experience. On the other hand, the characteristics of primary founders of North/West European firms are more linked to the importance of the participation to funded research programmes. This source of knowledge is related positively with age and education and negatively with experience.
Keywords: L26; J24; D83; 330; Entrepreneurship; Knowledge; Experience; Education; Human Capital